The Destruction of the Climate Spending State - Orford, Adam (Columbia Journal of Environmental Law, 2026)
The Biden Administration bet big on spending laws to forward its climate policies, creating a novel “climate spending state” in a field previously approached primarily through regulation. But the second Trump Administration, building on an aggressive theory of Presidential power, with support from bicameral Congressional majorities and a sympathetic Supreme Court, has dismantled the climate spending state with startling ease and speed. Although degradation of the federal workforce and legislative alterations to the tax code have played their part, it is the Trump Administration’s refusal to administer the spending laws enacted by prior Congresses that has had the most disruptive and immediate impact, and which has suddenly brought the obscure law of federal appropriations to the forefront of national legal consciousness. A detailed analysis of the ongoing destruction of the climate spending state reveals a sophisticated strategy of Presidential impoundment, administrative unilateralism, aggressive litigation, and Executive influence over Congress’s spending power, in a manner never before seen in the United States. The radical transformation of legal norms in budgetary processes has implications far beyond climate law, to the very fabric of the U.S. constitutional order.